Development and characterization of microsattelite Loci for the harvested limpets Patella Candei (D'orbigny, 1839) and Patella Aspera (Röding, 1798) using 454 sequencing - Rivas, Manuel (2014)
World Congress of Malacology, Ponta Delgada, July 22-28, 2013.